Spanish for beginners - Perez, Señor Ramonito (Mandaluyong City, Philippines : Books Atbp. Publishing Corp, 2015)
This book is the first module written by the author, comments and suggestions from the users and readers for the purpose of improving its content and approaches are very much welcome.
Leccion 1. Spanish alphabets, sounds and diphthongs -- Leccion 2. The christian prayers -- Leccion 3. Survival spanish expressions -- Leccion 4. The spanish-filipino vocabularies -- Leccion 5. The spanish articles -- Leccion 6. Los nombres (the nouns) -- Leccion 7. Adjectives -- Leccion 8. Verbos irregulares -- Leccion 9. Verbos irregulares -- Leccion 10. Pronombres -- Leccion 11. Other forms of adjectives -- Leccion 12. Regular verbs & their conjugations -- Leccion 13. The gerund forms of verb -- Leccion 14. Spanish numbers -- Leccion 15. The spanish prepositions -- Leccion 16. Adverbios.
Includes bibliographical references.
Keywords: SPANISH